STABILITAS TANAH LEMPUNG MENGGUNAKAN KAPUR DAN FLY ASH DENGAN PENGUJIAN CBR - Dimitri Yulianti; Ani Firda; Bahder Djohan; Indra Syahrul Fuad (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2023)
Clay soil is formed from the chemical weathering of rock components, resulting in microscopic and submicroscopic particles. Clay soil has low shear strength and high compressibility. Therefore, efforts to improve it are necessary to overcome instability and settlement issues. This paper discusses the influence of CBR values when clay soil is mixed with fly ash and lime. Four proposed compositions are considered using 10% fly ash and 10, 15, 20, and 25% lime contents. The research results show that the proposed compositions have higher CBR values compared to the original CBR of the clay soil. For example, a composition with 10% fly ash and 10% lime has a CBR value of 13.65%, while a composition with 10% fly ash and 25% lime has a CBR value of 8.61%. Nevertheless, both compositions still yield higher CBR values than the original CBR value of the clay soil which was determined as being equal to 7.79%.